Italian Physical Society:Electron and Photon Confinement in Semiconductor Nanostructures - Deveaud, B (IOS Press, 2013)
This Volume originates from the lectures delivered at the CL Course of the “Enrico Fermi” School, which was held in Varenna from June 25 to July 5, 2002. The purpose of the course was to give an overview of the physics of artificial semiconductor structures confining electrons and photons. The study of the light-matter interaction in this kind of systems is relevant both to fundamental Solid State Physics and to related fields like Quantum Optics. Furthermore, it furnishes the background for several applications in particular in the domain of optical devices, lasers, light-emitting diodes or photonic crystals. In recent years the research in this field has focused on the electronic and optical properties of confined semiconductor structures like Quantum Wells, Quantum Wires, Quantum Dots and semiconductor microcavities. In this context, several exciting effects have been observed. In particular, we mention the effects related to the microcavity polaritons, which are mixed electromagnetic radiation-exciton states inside a semiconductor microcavity.